Pengaruh penggunaan bahan ajar fisika terintegrasi kecerdasan sosial melalui model pembelajaran berbasis masalah terhadap pencapaian kompetensi peserta didik kelas X SMAN 16 Padang - rika septian amelia; Zulhendri Kamus; Renol Afrizon (PILLAR OF PHYSICS EDUCATION, 2019)
Increasing the achievement of learners' physical competencies can be done one of them by using a variety of teaching materials, as well as the use of learning models that can improve student learning activities. This study aims to determine the effect of the use of integrated physics teaching materials on social intelligence through a problem-based learning model towards the achievement of physics competencies of class X students of SMAN 16 Padang. This research is classified as Pre-Experimental Design with the design of Pretest- Posttest One Group Design. The population used is all students in class X 2018/2019. The sample is determined using purposive sampling technique. The data of this study include data on attitudes, knowledge and skills competency. After doing the research and continuing with analyzing the data it can be concluded that the use of integrated physics teaching materials social intelligence through problem-based learning models affects the achievement of knowledge competencies by 64.91% while the achievement of student skills competencies is 73.91%.